Foreign Direct Investment and Total Factor Productivity: Any Nexus?. (May 2020) - Abdullah, Mohammed; Chowdhury, Murshed
This study examines the impact of foreign direct investment (FDI) on the total factor productivity (TFP) of host countries. Extensions of the new growth theory provide a framework in which FDI increases the growth rate of a host country through technology transfer, diffusion and spillover effects. We construct four new series of TFP using the framework of neoclassical growth models. We also address the issue of endogeneity using the generalized method of moments. Our estimations using a balanced panel of 77 low- and middle-income countries suggest that FDI could not promote TFP in the countries studied. Our sensitivity analysis, in terms of alternative estimation methods, data, models and time period, reinforces the findings. We observe that the lack of absorptive capacity is likely to be an important reason for not having a direct relationship between FDI and TFP. JEL Classification: F21, F23, O33, F43, C33